Echocardiographic Strain Analysis for the Early Detection of Left Ventricular Systolic/Diastolic Dysfunction and Dyssynchrony in a Mouse Model of Physiological Aging. (18th June 2018) - de Lucia, Claudio; Wallner, Markus; Eaton, Deborah M; Zhao, Huaqing; Houser, Steven R; Koch, Walter J
Abstract: Heart disease is the leading cause of hospitalization and death worldwide, severely affecting health care costs. Aging is a significant risk factor for heart disease, and the senescent heart is characterized by structural and functional changes including diastolic and systolic dysfunction as well as left ventricular (LV) dyssynchrony. Speckle tracking–based strain echocardiography (STE) has been shown as a noninvasive, reproducible, and highly sensitive methodology to evaluate LV function in both animal models and humans. Herein, we describe the efficiency of this technique as a comprehensive and sensitive method for the detection of age-related cardiac dysfunction in mice. Compared with conventional echocardiographic measurements, radial and longitudinal strain, and reverse longitudinal strain were able to detect subtle changes in systolic and diastolic cardiac function in mice at an earlier time point during aging. Additionally, the data show a gradual and consistent decrease with age in regional contractility throughout the entire LV, in both radial and longitudinal axes. Furthermore, we observed that LV segmental dyssynchrony in longitudinal axis reliably differentiated between aged and young mice. Therefore, we propose the use of echocardiographic strain as a highly sensitive and accurate technology enabling and evaluating the effect of new treatments to fight age-induced cardiac disease.